Analysis Of Health Personnel Resources On The Finding Of Suspects In The Pulmonary Management Program At Tambusai Community Health Center, Rokan Hulu District: Analisis Sumber Daya Tenaga Kesehatan Terhadap Penemuan Suspec Dalam Program Penanggulangan TB Paru Di Puskesmas Tambusai Kabupaten Rokan Hulu - Muhammad Dahlan; Reno Renaldi; M.Dedi Widodo; Welly Sando; Dami Yanthi (Badnur Medisa Group, 2022)
Pulmonary tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis. These bacteria generally attack the lungs, such as lymph nodes, skin, digestive tract (intestines), the lining of the brain, and so on. Tambusai Public Health Center is the lowest suspected pulmonary tuberculosis finding, where data on pulmonary tuberculosis suspect findings in 2019 was 215 (21.2%) cases, in 2020 there were 198 (20%) cases, while in 2021 it was 140 (16%). The purpose of this study is to determine the analysis of health personnel resources on the discovery of suspects in the pulmonary tuberculosis control program at the Tambusai Health Center, Rokan Hulu Regency in 2022. This type of research is a case study with a qualitative method. The research subjects were the head of the puskesmas, the person in charge of the pulmonary tuberculosis program at the puskesmas, laboratory staff, and the families of patients with pulmonary tuberculosis. Research Time April-June 2022. Data collection was carried out by in-depth interviews, document searches and observations. The results showed that the determination of human resources was not in accordance with education in the tuberculosis control program while laboratory human resources were in accordance with their education, for the obstacles faced by human resources in carrying out suspect examinations in the tuberculosis control program itself but they could still be overcome, while for human resources training, it was carried out once in a week. 1 year, for the infrastructure is quite complete. It is recommended that the puskesmas should look for human resources personnel in accordance with the field and education of the pulmonary tuberculosis program, and conduct human resources training at least 2x in 1 year on a regular basis, as well as for infrastructure facilities in controlling the tuberculosis program in more detail, provide reports to the Department and as soon as possible get a TCM tool from Service for the fastest tuberculosis examination